Comparative Study: Implementing Numbered Heads Together and Team Games Tournament to Enhance Students' Knowledge on Passive and Active Voice Construction - Teedja, Katty Elizabeth Malta (LPPM Universitas Advent Indonesia, 2019)
This study intends to find out what is the initial knowledge of the students before they were treated using Numbered Heads Together (NHT) and Team Games Tournament (TGT), ascertain of the significant difference between these two teaching strategies, and to know the responses of the students after they taught using Numbered Heads Together and Team Games Tournament are the aims of this research. This is a quantitative study with comparative design to know the students' knowledge of active and passive construction test. The research instrument of this study is pre-and-posttest. This study was conducted among seventh-grade students at SMPN 10 Cimahi. The results of this study showed that the initial score for both respondents is quite similar to the score for NHT group is 59.07 and for TGT group is 58.33. It is also known that there is a significant difference in students' knowledge on active and passive voice construction between students who are taught with Numbered Heads Together and those who are taught with Team Games Tournament showed by the result of the mean differences from both groups are 0.005 < 0.05. The questionnaire's result also supports that both teaching strategies are eligible to be applied in teaching active and passive voice construction with the score for NHT class is 64.83% and for the TGT class is 63.34%, it can be categorized as